2010
DOI: 10.1002/cncr.25672
|View full text |Cite
|
Sign up to set email alerts
|

Experimental therapeutics for patients with myeloproliferative neoplasias

Abstract: Philadelphia chromosome (Ph)‐negative myeloproliferative neoplasms (MPNs) are characterized by stem cell‐derived, unrestrained clonal myeloproliferation. The World Health Organization classification system, proposed in 2008, identifies 7 distinct categories of Ph‐negative MPNs including essential thrombocythemia (ET); polycythemia vera (PV); primary myelofibrosis (PMF); mastocytosis; chronic eosinophilic leukemia; chronic neutrophilic leukemia; and MPN, unclassifiable. For many years, the treatment of ET, PV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…In hematologic neoplasms such as chronic myelomonocytic leukemia and acute myeloid leukemia JAK2 is constitutively activated because of a mutation (Levine et al,2005; Baxter et al,2005; Tefferi et al,2005; Bina et al,2010), while aberrant JAK activity due to overexpression of wild‐type JAK2 is also associated with a number of solid tumors, including gastric carcinoma, hepatocellular carcinoma, and head and neck squamous cell carcinoma (Lee et al,2006; Fuke et al,2007; Hedvat et al,2009; Kupferman et al,2009). In different experimental models, tumorigenesis is associated with increased activity of JAK2, and functional ablation of JAK2 protects against the onset of various tumors (Sakamoto et al,2009; He and Zhang,2010; Agrawal et al,2011). Studies in our laboratory showed that wild‐type JAK2 is significantly upregulated in primary gastric cancers, and down‐regulation of JAK2 significantly suppresses the proliferation of gastric cancer cells, suggesting that JAK2 may play a key role in gastric carcinogenesis (Ding et al,2010).…”
Section: Introductionmentioning
confidence: 99%
“…In hematologic neoplasms such as chronic myelomonocytic leukemia and acute myeloid leukemia JAK2 is constitutively activated because of a mutation (Levine et al,2005; Baxter et al,2005; Tefferi et al,2005; Bina et al,2010), while aberrant JAK activity due to overexpression of wild‐type JAK2 is also associated with a number of solid tumors, including gastric carcinoma, hepatocellular carcinoma, and head and neck squamous cell carcinoma (Lee et al,2006; Fuke et al,2007; Hedvat et al,2009; Kupferman et al,2009). In different experimental models, tumorigenesis is associated with increased activity of JAK2, and functional ablation of JAK2 protects against the onset of various tumors (Sakamoto et al,2009; He and Zhang,2010; Agrawal et al,2011). Studies in our laboratory showed that wild‐type JAK2 is significantly upregulated in primary gastric cancers, and down‐regulation of JAK2 significantly suppresses the proliferation of gastric cancer cells, suggesting that JAK2 may play a key role in gastric carcinogenesis (Ding et al,2010).…”
Section: Introductionmentioning
confidence: 99%
“…Drugs such as hydroxyurea and interferon-alpha have modest activity in controlling splenomegaly and leucocytosis in patients with PMF, and favourable responses to thalidomide and lenalidomide, chiefly in the form of improved haemoglobin and platelet counts, have been reported in a small subset of patients. 31 , 32 Ruxolitinib (a JAK-1/2 inhibitor) was recently approved for the treatment of intermediate and high-risk MF, including PMF, post-PV MF or post-ET MF, with ⩾35 percent reduction in splenic volume in 41.9% of patients, which was maintained for 48 weeks in the majority of patients with such a response. 5 , 33 In the current phase II exploratory trial, only one patient had confirmed disease response (anaemia improvement), whereas most patients had stable disease as best response.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines and growth factors activate the extracellular portion of their cognate receptors [41,42], which in turn promotes the recruitment of JAK proteins to associate closely with the intracellular portion of these receptors and the activation of the JAK proteins via phosphorylation (Figure 1). Phosphorylation of JAK proteins, in turn, leads to the phosphorylation and activation of several intracellular downstream signaling proteins, such as STAT proteins [42].…”
Section: Normal Jak-stat Signalingmentioning
confidence: 99%
“…Phosphorylation of JAK proteins, in turn, leads to the phosphorylation and activation of several intracellular downstream signaling proteins, such as STAT proteins [42]. Phosphorylated STATs translocate to the nucleus and act as inducible nuclear-transcription factors [42], which lead to transcriptional modulation and eventual expression of cellular, molecular and (patho)-physiologic actions that were promoted by the initial signal (ligand).…”
Section: Normal Jak-stat Signalingmentioning
confidence: 99%
See 1 more Smart Citation